Floral Closure in Lesser Celandine (Ficaria verna) Protects Anthers from Pollen Flushing and Preserves Pollen Viability - Pavol Prokop; Zuzana Provazník; Kristián Tučník (Plants)
Flower closure is a widespread yet understudied trait that may serve multiple functions in the success of plant reproduction. In this study, we investigated the role of flower closure in protecting pollen from rain-induced loss in lesser celandine (Ficaria verna Huds., 1762), an early-flowering species vulnerable to spring rains. Through simulated and natural rain experiments, we found that the flowers that were prevented from closing retained significantly fewer pollen grains compared to the control flowers. This demonstrates that flower closure effectively protects pollen from rain-induced flushing, thus enhancing reproductive success. Furthermore, flowers that were prevented from closing had fewer viable pollen grains than control flowers. We propose that the evolution of petal movement in F. verna was primarily driven by pressures favoring petal movement that protected pollen, with secondary contributions from herbivore avoidance. Flowers are unable to discriminate between low luminosity caused by cloudy weather and night, thus responding to both. Future studies should explore the relative importance of primary and secondary evolutionary drivers of flower closure across species, particularly in early-flowering plants facing complex environmental challenges.